PRE-HISTORIC ROCK PAINTING: DICKEN (DISTRICT NEEMUCH): पूर्व ऐतिहासिक शैलचित्र: डिकेन (जिला नीमच) - Jain, Sushma (International Journal of Research -GRANTHAALAYAH, 2020)
Humans have been lovers of beauty and art from the beginning. Like human life, the history of the rise of art is very mysterious, vast and unknown. It is not easy to present the facts of past merged in innumerable layers of time, even today we have a complete lack of means and evidence. The places where rock paintings have been found in India are still located in dense forests far away from human reach. All these prehistoric arts are pre-human. With these inscriptions we not only gain knowledge of the nature, life, struggle and conditions of the primitive human, but we also get the proof of the aesthetic sense of creativity in his consciousness. These rock paintings did not come to light suddenly, after a decade of prehistoric paintings of Spain, France, rock paintings also became a topic of discussion in India. Credit for the discovery of these Shailashrayi paintings first goes to Carlile and Cuckburn. 3 मानव प्रारम्भ से ही सौंदर्य एवं कला प्रेमी रहा है । मानव जीवन की भाँति कला के उदय का इतिहास अत्यंत रहस्यमय, विराट तथा अज्ञात है । काल की असंख्य परतों में विलीन अतीत के तथ्यों को मूर्त रूप में प्रस्तुत करना सहज नहीं है, आज भी हमारे पास साधनों एवं प्रमाणों का सर्वथा अभाव है।1 भारत में शैलचित्र जिन स्थानों पर प्राप्त हुए हैं वे स्थान आज भी मानव की पहुंँच से दूर घने जंगलों में स्थित हैं।2 ये समस्त प्रागैतिहासिक कलाएँ मानव के सभ्य होने से पूर्व की हैं । इन शिलाचित्रों से हम न केवल आदिम मानव के स्वभाव, जीवन, संघर्ष तथा उसकी परिस्थितियों का ज्ञान प्राप्त करते हैं वरन् उसकी चेतना में व्याप्त सृजनशीलता से युक्त सौंदर्य बोध का भी प्रमाण पाते हैं । ये शैलचित्र अचानक ही प्रकाश में नहीं आ गए स्पेन, फ्रांस के प्रागैतिहासिक चित्रों के एक दशक पश्चात् भारत में भी शैलचित्र चर्चा का विषय बन गए । इन शैलाश्रयी चित्रों की खोज का श्रेय सर्वप्रथम कार्लाइल तथा काकबर्न को जाता है ।3